(untitled) ("Temas Sociais" Journal, 2022)
This article aimed to understand the conjugal violence in Portugal during the last decade (2010-2020). Thus, quantitative data from public institutes were researched and systematized. It was found that, within the crime of domestic violence, conjugal violence was the most frequent type of violence in Portugal, with the victims mostly being women, and the denounced, men. Although, in Portugal, there has been an effort to develop and implement policy measures to prevent and combat violence against women and domestic violence, these have not translated into an effective reduction in the number of cases of conjugal violence.